A qualitative Study of Czech non-believing Students - Říhová, Nikola (Univerzita Karlova, Fakulta sociálních věd, 2023)
In my bachelor's thesis I focus on what it means for one to be a non-believer, supported by various statistics and data that examine non-believers in the world and in the Czech Republic. Using a qualitative process of data collection, I thus explore what my informants' individual beliefs are within the topic of non-religion, as well as how they themselves reflect on the sources of these beliefs. Specifically, this thesis then seeks to grasp these themes through two main theoretical frameworks. Firstly, identity formation, which is introduced through the theory of G.H. Mead, who points to the so- called significant other in this process. At the same time, I introduce the Social Identity Theory by H. Tajfel and J. Turner, which discusses the importance of social groups on individual identity formation. This social group is represented in my thesis as a group of non-believers, but it can be further divided into other subgroups. This is followed by a second framework where I present M. Weber's secularization theory and more specifically his disenchantment of the world, but this is complemented by its critique, represented for example by P. Berger, who in turn writes about the re-enchantment of the world. Using these aforementioned ideas, then, I want to point out that the topic of non-believers is a. V mojí bakalářské práci se zaměřuji s podporou různých statistik a dat, které zkoumají nevěřící ve světě a v České republice, co to pro jednoho znamená být nevěřící. Pomocí kvalitativního procesu sběru dat, tak zkoumám, co jsou jednotlivé přesvědčení mých informantů v rámci tématu nenábožneství a zároveň jak oni sami reflektují zdroje těchto přesvědčení. Specificky se pak tato práce snaží uchopit tato témata na základě dvou hlavních teoretických rámců. Zaprvé formování identity, což je představeno pomocí teorie G.H. Meada, který v tomto procesu poukazuje na tzv. významné druhé. Zároveň představuji teorii sociální identity od H. Tajfela a J. Turnera, která pojednává o důležitosti sociálních skupin na formaci identity ...